Teacher-student interaction in English class at state senior high school in Banjarbaru - Fadillah, Ridha; Ridha, Muhammad; Juhaidi, Ahmad (Englisia Journal, 2022)
This study investigated the interaction happened in English class at State Senior High School 3 in Banjarbaru, South Kalimantan. English teacher and Class 11 students at Senior High school 3 in Banjarbaru were the research subjects. The object of the research was classroom interaction. Purposive sampling was used in determining the research sample. Flanders Interaction Analysis Category as an observation guide and interviews were used to collect the data in the class. The results indicate that two-way communication among teacher, student, and students occurred in English class. The findings revealed that teacher-talk was 42.79% and student-talk was 53.79%, while silence or confusion was 3.40%. It indicated that two-way communication between teacher and students occurred in English Class. It shows that students are the center of learning process and the students are active during English learning process. However, this study differs from previous studies as the Flanders Interaction Analysis Category used here was analyzed according to the perspectives of foreign language anxiety.